An Analysis of Online Corrective Feedback Implementation in Writing Class - Titik Lina Widyaningsih (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2018)
In an academic setting, writing is a skill which requires a high level of cognitive competencies. It means that as the students of university should prepare themselves for always being active learners to improve their level of cognitive competencies used for their writing skills. Nowadays, the range of technologies are available to be used in the class. To make the atmosphere in the class be more challenging and interesting, there are many lecturers use technology in their writing class. As one of example, utilizing technology in writing class, especially in providing the feedback for the students to enhance students’ written performance. This research focused on analyzing the implementation of online corrective feedback (via e-mail) in the writing class. This research was conducted in the second semester students of English Department. The researcher used qualitative method to conduct this research. There were three kinds of instruments used in this research. There were interview, observation, and questionnaire. The result of this research showed that the implementation of online corrective feedback was really effective for the students’ writing skills improvement. The lecturer’s activities, the students’ responses, and the online corrective feedback implementation itself were the factors that could not be separated in gaining a successful teaching and learning process in writing class.